2015
DOI: 10.1002/ana.24305
|View full text |Cite
|
Sign up to set email alerts
|

Coding mutations in SORL1 and Alzheimer disease

Abstract: Importance Common single nucleotide polymorphisms in the SORL1 gene have been associated with late onset Alzheimer’s disease (LOAD) but causal variants have not been fully characterized nor has the mechanism been established. Objective To identify functional SORL1 mutations in patients with LOAD. Design and Participants This was a family- and cohort-based genetic association study. Caribbean Hispanics with familial and sporadic LOAD and similarly aged controls recruited from the United States and the Domin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
166
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 167 publications
(180 citation statements)
references
References 32 publications
13
166
0
1
Order By: Relevance
“…More, the investigation of an EOAD patient-control cohort confirmed the role of rare nonsynonymous coding variants in SORL1 as risk factor for EOAD (Table 2), with the association signal driven by familial patients [77]. Also, both common and rare, noncoding and coding variants in SORL1 have been associated with increased risk of LOAD [113][114][115]. Three SORL1 coding mutations (p.E270K and p.T947M, p.A528T) identified in a family-based and cohort-based association study on LOAD have been shown to increase Ab40 and/or Ab42 secretion when expressed in vitro [115].…”
Section: The Missing Genetics Of Eoadmentioning
confidence: 60%
See 1 more Smart Citation
“…More, the investigation of an EOAD patient-control cohort confirmed the role of rare nonsynonymous coding variants in SORL1 as risk factor for EOAD (Table 2), with the association signal driven by familial patients [77]. Also, both common and rare, noncoding and coding variants in SORL1 have been associated with increased risk of LOAD [113][114][115]. Three SORL1 coding mutations (p.E270K and p.T947M, p.A528T) identified in a family-based and cohort-based association study on LOAD have been shown to increase Ab40 and/or Ab42 secretion when expressed in vitro [115].…”
Section: The Missing Genetics Of Eoadmentioning
confidence: 60%
“…Also, both common and rare, noncoding and coding variants in SORL1 have been associated with increased risk of LOAD [113][114][115]. Three SORL1 coding mutations (p.E270K and p.T947M, p.A528T) identified in a family-based and cohort-based association study on LOAD have been shown to increase Ab40 and/or Ab42 secretion when expressed in vitro [115]. These studies reinforced the role of rare variants in SORL1 in both EOAD and LOAD risk.…”
Section: The Missing Genetics Of Eoadmentioning
confidence: 65%
“…We also included known early‐onset AD genes and genes implicated in earlier sequencing efforts in LOAD 1, 2, 3, 4, 5, 6, 8, 9, 10, 11, 12, 13, 14, 15, 16. Candidate genes evaluated included: APP, PSEN1, PSEN2, GRN, MAPT, TREM2, PLD3, APOE, ABCA7, SORL1, CR1, BIN1, CD2AP, EPHA1, CLU, MS4A6A, PICALM, CD33, HLA‐DRB5, HLA‐DRB1, PTK2B, SLC24A4, RIN3, INPP5D, MEF2C, NME8, ZCWPW1, CELF1, FERMT2, CASS4, TREML2, and AKAP9 .…”
Section: Methodsmentioning
confidence: 99%
“…It is also possible that these causal variants are rare and have large effects, such as TREM2, 7, 8, 9, 10, 11, 12, 13 and are not covered by commercially available GWAS platforms. In fact, putatively damaging variants have already been identified (for example TREM2 , SORL1, and ABCA7 ) in some of these LOAD susceptibility loci, advancing our understanding of disease risk 14, 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…After focusing on cases with a positive family history ( n = 205), the OR increased to 8.86 (95% CI = 3.35-27.31), and the p value reached exome-wide significance ( p = 3.82 × 10 -7 ). The association of SORL1 rare variants was replicated in a Belgian case-control study based on targeted sequencing of 1,255 EOAD patients and 1,938 controls of European ancestry (SKAT-O p value = 0.0001) [79] , and another study investigated SORL1 rare variants in LOAD families providing some more functional data [80] .…”
Section: The Sorl1 Genementioning
confidence: 83%